KOMBINASI STRATEGI BERNYANYI DAN BERMAIN: UPAYA DALAM MENUMBUHKAN MOTIVASI MAHASISWA TADRIS BIOLOGI (TBG) DALAM PEMBELAJARAN BAHASA ARAB - Mubarak, Mahfuz Rizqi; Ahmadi, Ahmadi; Audina, Noor Amalina (Departemen Pendidikan Bahasa Arab, 2020)
This study aims to explore the process of lecturing Arabic by implementing a combination of singing and playing strategies. As for the main problems in this study are: (1) what is the process of implementing a combination of singing and playing strategies in Arabic lectures for Tadris Biology Study Program students? (2 how do their perceptions of the results of Arabic lectures by combining the two strategies?. This research uses a descriptive qualitative approach with triangulation techniques. The results of this study indicate that the implementation of a combination of singing and playing strategies uses the following steps: (1) The lecturer started the Arabic lecture by singing Arabic songs that the Lecturer got while still teaching Arabic at the Al-Azhar Pare Institute, Kediri, East Java, (2) The lecturer explained the theme of the material and the purpose of the lecture to be held, (3) The lecturer implemented the